THE INTERACTION OF HYDROPHILIC POLYMERS WITH TEAR FILM COMPONENTS IN DRY EYE SYNDROME THERAPY – MAKING THE RIGHT CHOICE - Petar Eftimov; Nadezhda Stefanova; Nikola Peev; Georgi Georgiev (Science & Research)

(untitled)
The need for the use of quality ophthalmological compositions for supplementary therapy of the dry eye syndrome (DES) is ever increasing. This study aims at elucidation of biophysical interactions between four prospective hydrophilic polymers – gellan gel (GG), carboxymethyl-celulose (CMC), hyaluronic acid (HA) and cross-linked hyaluronic acid (CHA) and human meibum (lipid component of the tear film). Various therapeutically accepted concentrations of the aforementioned polymers mixed with the meibum from healthy volunteers were evaluated by measurement of the film pressure. Ferning patterns of evaporated micro drops (V=3μl) from the polymers were observed and compared. The wettability of the polymers was evaluated by axisymmetric drop-shape analysis (ADSA). In lower concentrations (0.0001% and 0.001%) CMC outperformed the rest of the polymers, but in the higher concentrations (0.01%, 0.05% and 0.1%) it generated lower film pressures. Complex intermolecular rearrangements of the meibum may be responsible for that behavior. The results will contribute in getting more correct understanding of the action of some medications, used for treatment of DES and for corrections in calculating the precise concentration of their active compounds.